Efforts to Improve Teacher Competence in Developing Science, Technology, Engineering, and Mathematics Based Learning Tools Through in House Training Activities - Mu'jizat, Mu'jizat (Universitas Negeri Makassar, 2022)
Science, Technology, Engineering, and Mathematics (STEM) education is integrated learning between science, technology, engineering, and mathematics to develop students' creativity through problem-solving processes in everyday life. The purpose of this research is to improve the competence of SMAN 3 Sigi teachers in developing STEM-based learning tools through In House Training (iHT) activities in Semester 1 of the 2021/2022 Academic Year. This research is a classroom action research. The research subjects are 10 teachers at SMAN 3 Sigi, while the object of the research is the improvement of teacher competence in developing STEM-based learning tools through iHT activities. While the data collection method used is observation and documentation. Furthermore, data analysis was carried out through three stages, namely reducing data, describing data, and making conclusions. The results of the study indicate that increasing teacher competence in developing STEM-based learning tools through iHT activities that emphasize collaborative consultative methods will provide opportunities for sharing between one principal and teacher as well as teachers and other teachers. Thus, the understanding and ability, and competence of teachers in the development of STEM-based learning tools can be improved both in theory and in implementation.